Mentoring-Based Entrepreneurship Training To Improve Community Empowerment - Hidayat, Dayat; Hoerniasih, Nia; Hermawan, Iwan; Mobo, Froilan Delute; Rashid, Salman (Journal of Nonformal Education, 2026)
This study aims to analyse the effectiveness of community empowerment through entrepreneurship training and guidance in improving the entrepreneurial competence and economic self-sufficiency of individuals living in Karawang Regency. The research methodology uses a mixed-method approach characterised by a sequential explanatory design. Quantitative data were collected through a pretest-posttest design with entrepreneurship training participants across various CLCs, while qualitative data were collected through interviews, observations, and documentation. Quantitative analysis was conducted using paired t-tests, N-Gain assessments, and effect size calculations (Cohen’s d), while the qualitative study followed Miles and Huberman’s interactive model. The analysis showed a statistically significant increase across all dimensions of entrepreneurial ability, including managerial, conceptual, interpersonal, decision-making, and time management competencies. The participants’ average scores increased from the low category in the pretest to the exceptional category in the posttest. The N-Gain value is high (≥0.86), and the effect size indicates a substantial impact (Cohen's d > 0.80), suggesting the model’s significant effectiveness. Qualitative findings reinforce the importance of participatory engagement and continuous guidance in promoting greater business autonomy, improved decision-making capacity, and the sustainability of entrepreneurial efforts. Collectively, these findings prove that the combination of systematic training and entrepreneurial mentoring is an effective and sustainable paradigm for community empowerment.